Revealing the Role of Vapor Flux in Chemical Vapor Deposition Growth of Bi2O2Se for Photodetectors - Qin Huang; Jiqing Nie; Jian Li; Meng Wang; Changyuan Ding; Haiyan Nan; Xiaofeng Gu; Zhengyang Cai (Nanomaterials)
Two-dimensional (2D) materials are regarded as key foundational materials for next-generation optoelectronic devices. As a promising new type of 2D layered semiconductor, Bi2O2Se has emerged as a strong candidate for high-performance opto-electronic devices due to its high carrier mobility, tunable bandgap, and excellent environmental stability. However, achieving precise control over Bi2O2Se growth to obtain high-quality Bi2O2Se remains a challenge in the field. In this study, we employed chemical vapor deposition (CVD) to grow thin-layer 2D Bi2O2Se flakes. We further used a transport model and thermodynamic Arrhenius fitting to analyze the relationship between vapor flux and the properties of the flakes. Density functional theory was used to study the electronic structure of the as-grown samples. The electrical and optoelectronic results demonstrate that Bi2O2Se-based FETs exhibit good performance in terms of mobility (129 cm2V−1s−1), on/off ratio (4.51 × 105), and photoresponsivity (94.98 AW−1). This work provides a new way to study the influence of vapor flux on the sizes and shapes of Bi2O2Se flakes for photodetectors.